What the Yield Curves say About Inflation Does it Change Over Time? - Schich, Sebastian (OECD Publishing, 2000)
The paper investigates the information content of yield curves regarding future inflation, using the example of the G-7 countries. The empirical results show substantial variation of results across countries, and a significant information content is identified for the United States, the United Kingdom, Germany and Canada. The results also vary with the choice of the sample period. Nevertheless, the relationship appears to be structurally stable in Germany and Canada. By contrast, there is evidence for structural instability in the United States and the United Kingdom, possibly reflecting changes in their monetary policy regimes ...
Keywords: Economics